Strategi Perbaikan Implementasi Manajemen Keselamatan dan Kesehatan Kerja (K3) TPAS Wisata Edukasi Talangagung Kabupaten Malang - Dhymas Sulistyono Putro (Jurnal Serambi Engineering, 2021)
The operation of the Talangagung Edu-Tourism Landfill applies a sanitary landfill system, which requires a workforce  to operate  optimally. These workers may be exposed to work  accidents and occupational diseases when the Landfill is operating, which come from various sources of OHS hazards. Efforts to reduce the risk of work accidents and occupational diseases consist of managing  OHS in the working  environment of the Talangagung Edu-Tourism Landfill. The goal of this study is to evaluate the application and provide recommendations to  improving the application of OHS management at  the Edu-Tourism Landfill in Talangagung. Thus, the Talangagung Edu-Tourism Landfill can maximize the volume of waste and educational tourism facilities. This study involved 16 respondents who were divided into workers and decision-makers by selective  sampling in the operation of the Talangagung Edu-Tourism Landfill with data collection by observation, interviews, and questionnaires. The results of this study show that the Talangagung Edu-Tourism Landfill has implemented OHS management but the need to formulate new OHS management, to achieve  maximum results. The priority strategy in efforts to improve OHS management is to "enhance  awareness of OHS management" where there is a plan to implement  the strategy to facilitate  implementation of  the strategy in the work environment.